2008
DOI: 10.1590/s0001-37652008000200012
|View full text |Cite
|
Sign up to set email alerts
|

The influence of bromazepam on cortical power distribution

Abstract: The EEG has been widely employed in the assessment of electrophysiological changes induced by distinct medications. Its sensibility in detecting alterations produced by a specific substance may be enhanced by methods of quantitative analyses (qEEG). The present study aimed at investigating the modulatory effects of bromazepam on brain dynamics. The effects of bromazepam (3mg) on EEG power distribution were tested in 10 healthy individuals, in a double-blind experiment. The electrophysiological measure was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…These effects could be due to increasing the reaction time during the execution of tasks; could induce greater attention level or reduce the mental effort in the performance of motor tasks (Cunha et al, 2008). Besides, Sampaio et al (2008) showed positive effects of the acute use of bromazepam during the execution of visuomotor tasks, due to a significant reduction of stress and anxiety. However, there is controversy regarding the effects of bromazepam (6mg) in the target shooting tasks, since the task requires cognitive perception and a motor response depending on attention and fine motor control for the trigger pull (Janelle et al, 2000;Kerick et al, 2004;Deeny et al, 2009;Hatfield et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects could be due to increasing the reaction time during the execution of tasks; could induce greater attention level or reduce the mental effort in the performance of motor tasks (Cunha et al, 2008). Besides, Sampaio et al (2008) showed positive effects of the acute use of bromazepam during the execution of visuomotor tasks, due to a significant reduction of stress and anxiety. However, there is controversy regarding the effects of bromazepam (6mg) in the target shooting tasks, since the task requires cognitive perception and a motor response depending on attention and fine motor control for the trigger pull (Janelle et al, 2000;Kerick et al, 2004;Deeny et al, 2009;Hatfield et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the exploration, understanding, and monitoring of the action of BDZs in cortical activity have been analyzed in electroencephalography (EEG) (Saletu et al, 2002;Sampaio et al, 2008;Salles et al, 2006). The literature search to trace an association profile of drugs with neurophysiological functions and behavioral performance, and thus, the sensitivity and differential performance to stimuli has been associated with cortical activation patterns through energy measures within the range of theta frequency (Machado et al, 2009;Gongora et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Cognitive neuroscience has been trying to understand how this stream of processes occurs under the effect of anxiolytic drugs, [7][8][9][10] since increasing evidence is showing that these drugs could shift cognitive functions. [11][12][13] Benzodiazepines have been used in several neurophysiological trials because of their constant use in anxiety symptoms. [14][15][16] The most prescribed and used benzodiazepine around the world is bromazepam; this drug has been employed in several trials to understand how the brain areas involved in cognitive processes operate under its influence.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 On the other hand, positive effects on task performance were demonstrated when low doses were administered because of their power to decrease internal stress and anxiety. 13,22 To evaluate the electrophysiological changes resulting from the administration of drugs, quantitative electroencephalographic (qEEG) recordings have been used together with sensorimotor integration tasks to investigate cognitive processes. 16 These tasks play an important role in understanding attention and sensoriomotor integration processes.…”
Section: Introductionmentioning
confidence: 99%
“…Bromazepam is a drug that has been widely used in psychiatry disorders for four decades (Blanco, 2002;Sampaio et al, 2008), with selective anxiolytic, anticonvulsant, myorelaxant and hypnotic actions (Podilskyi. et.…”
Section: Introductionmentioning
confidence: 99%